Teacher Mentoring to Enhance Quran Reading Skills Using Card-Shot Hijaiyah Letter Media at Islamic Education of Qur’an - Zakiyah BZ BZ; Firdaus Nuzulah; Lailatul Muarifah; Zulfa Umi Zakiyah; Wiwis Rohmatul Ummah; Alfina Tahta Alfina; Dea Ayu Rozikin (Education and Sociedad Journal, 2024)
This study aims to improve the effectiveness of teaching methods used by educators in enhancing students’ Quran reading skills at Islamic education institutions. This study highlights the challenges faced by traditional teaching methods, which often fail to engage students and support their understanding of Arabic letters (Hijaiyah). This study employed qualitative methods within a descriptive framework to mentor teachers in implementing the Card Shot Two and Four approach. The program included systematic training sessions and continuous mentoring to empower educators with improved skills and knowledge in delivering Quran reading lessons. The findings indicate that the use of this innovative teaching method significantly enhances students’ ability to recognize and read Hijaiyah letters, increasing both their proficiency and enthusiasm for learning the Quran. This research is expected to provide a contribution in the form of practical solutions to the challenges of traditional Qur'an teaching methods.